2013
DOI: 10.1159/000353308
|View full text |Cite
|
Sign up to set email alerts
|

Retrotransposons Represent the Most Labile Fraction for Genomic Rearrangements in Polyploid Plant Species

Abstract: Understanding how increased genome size and diversity within polyploid genomes impacts plant evolution and breeding continues to be challenging. Although historical studies by McClintock suggested the importance of transposable elements mediated by polyploidisation on genomic changes, data from plant crosses remain scarce. Despite the absence of a conclusive proof regarding autonomous retrotransposon movement in synthetic allopolyploids, the transposition of retrotransposons and their ubiquitous dispersion in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
(79 reference statements)
2
8
0
Order By: Relevance
“…IRAP PCR was performed in a 20 µL reaction mixture as previously described [38], using primers targeting the LTR of retrotransposons Nikita (5 1 -CGCTCCAGCGGTACTGCC) [39], Tat-1 (5 1 -TCCTCGTAAAACAACCACAAG), and Athila4-6 (5 1 -AAATGGATGCTCAAAACATGC) [19]. PCR products were separated by 1.7% agarose gel electrophoresis and detected by Ethidium Bromide staining.…”
Section: Irapmentioning
confidence: 99%
See 1 more Smart Citation
“…IRAP PCR was performed in a 20 µL reaction mixture as previously described [38], using primers targeting the LTR of retrotransposons Nikita (5 1 -CGCTCCAGCGGTACTGCC) [39], Tat-1 (5 1 -TCCTCGTAAAACAACCACAAG), and Athila4-6 (5 1 -AAATGGATGCTCAAAACATGC) [19]. PCR products were separated by 1.7% agarose gel electrophoresis and detected by Ethidium Bromide staining.…”
Section: Irapmentioning
confidence: 99%
“…IRAP methodology was used to target three distinct retrotransposable elements: Nikita (identified in barley [39]), Tat-1 [44] and Athila4-6 [45] (the last two from A. thaliana). These retrotransposons have been previously used to study genome diversity in other species besides the ones where they were identified [19,33,34,46]. They were selected to produce consistent banding profiles with easily distinguishable bands allowing the assessment of faba bean genotypes.…”
Section: Irap Analysis Of Genomic Diversitymentioning
confidence: 99%
“…When first discovered, TEs were considered as selfish or junk DNA, but they are now recognized as key components of genome evolution and diversification, as well as gene regulation (Feschotte and Pritham, 2007;Volff, 2006). TEs constitute a considerable fraction of the eukaryotic genome, and LTR retrotransposons are particularly abundant in higher-plant genomes (Bento et al, 2013;Tenaillon et al, 2010). Wide variations of genome size exist among plant species, and a difference of over 2000-fold has been reported between Genlisea margaretae Hutch.…”
Section: Discussionmentioning
confidence: 99%
“…Wide variations of genome size exist among plant species, and a difference of over 2000-fold has been reported between Genlisea margaretae Hutch. (63.4 Mbp) and Paris japonica (149,000 Mbp) (Pellicer et al, 2010); these differences are thought to have been driven by factors such as polyploidization and TE amplification (Bento et al, 2013;Tenaillon et al, 2010). In fact, plant genome size and TE (especially retrotransposon) content are well correlated (Tenaillon et al, 2010): plant species with huge genomes, such as maize and barley, tend to have higher proportions of TEs (> 85%), whereas plant species with smaller genomes, such as Arabidopsis thaliana and Brachypodium distachyon, show lower levels (20%-30%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation